Efficiency Assessment for Indoor Microwave Wireless Power Transmission Systems - Bahrampour, Sohrab (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Keeping the power hungry, smart wireless communication devices up and running became a challenging issue due to the need for continuous supply of battery power required for fulfilling all the functions. Since the battery capacity is limited, it needs to be recharged as often as possible. Hence, rather than spreading wires all around, it is a promising solution to cover the medium with electricity wirelessly or create charging points around residential premises based on Wireless Power Transmission technology. The work presented here involves investigation of the possibility of providing wireless charging points within a room and analyzing the choice of best frequency and best pulse shape for transmitting power wirelessly within a distance smaller than 10 m in order to charge batteries of such devices as smart phones. The parameters that can be adjusted to maximize efficiency of wireless power transmission and the relationship between the choice of frequency, pulse shape and distance is investigated. Antenna design will be left as a subject for future study. Keywords: Microwave, Wireless, Power, Transmission, International Telecommunication Unity (ITU) model, Indoor, Propagation, Smart phone, Battery

ÖZ: Akıllı kablosuz iletişim araçlarının sorunsuz çalışır durumda tutmak, bütün işlevlerini yerine getirmeleri için gerekli sürekli enerji ihtiyaçları nedeniyle, zorlu bir konu haline gelmiştir. Pil kapasite sınırlı olduğu için bu tür cihazlar sık sık şarj edilmelidir. Her yere kablo döşemek yerine; kablosuz güz iletimi teknolojisiyle ortamı kablosuz şekilde elektriklendirmek veya evler içinde kablosuz şarj etme noktaları oluşturmak gelecek vaad eden bir çözüm olabilir. Bu çalışmada bir oda içinde akıllı telefonlar gibi araçların pillerini şarj etmek için kablosuz şarj etme noktaları oluşturma olasılığı araştırılmış ve 10 m’den az uzaklığa kablosuz güç iletimi için en iyi frekans ve dalga şekli analiz edilmiştir. Kablosuz güç iletiminin verimini arttırmak için ayarlanan parametreler; frekans seçimi, dalga şekli ve mesafe arasındaki ilişki araştırılmıştır. Anten tasarımı gelecek çalışmaları için bir konu olarak bırakılmıştır. Anahtar Kelimeler: Mikrodalga, Kablosuz, Enerji, İletim, İTÜ modeli, İç mekan, Yayılım, Akıllı telefon, Pil
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2015. Supervisor: Prof. Dr. Hasan Amca.
Keywords: Electrical and Electronic Engineering; Wireless communication systems - Mobile; communication systems - Microwave communication systems; Microwave; Wireless; Transmission; Power; International Telecommunication Unity (ITU) model; Indoor; Propagation; Smart; phone; Battery